A MXene-graphene oxide composite film and its preparation method and application

Through the composite and oxidation and deterioration technology of MXene and graphene oxide, the problems of low stability and retention of existing filter membrane materials are solved, and the MXene-graphene oxide composite membrane with high water flux and high retention are achieved, which is suitable for industrial wastewater treatment.

CN119056270BActive Publication Date: 2025-04-01Yellow River Institute of Ecological and Environmental Sciences
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411417321.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-04-01
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing water treatment filter membrane materials have poor stability, are not resistant to acid and alkali, have low pollutant retention rates, and are difficult to achieve bidirectional balance of water flux and retention rates, which cannot meet the needs of high water flux and high retention rates.

Method used

By compounding MXene with graphene oxide, a specific preparation method is used to oxidize and deteriorate the MXene dispersion, forming TiO2 with a 0-dimensional/2-dimensional structure, enhancing water flux and improving interception.

Benefits of technology

The comprehensive performance of high water flux and high interception is achieved. The pure water flux reaches more than 650Lm-2h-1bar-1, the dye removal rate is as high as more than 90%, and the preparation method is simple and easy to operate, suitable for large-scale use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119056270B_ABST
    Figure CN119056270B_ABST
Patent Text Reader

Abstract

The present invention provides a MXene-graphene oxide composite membrane and its preparation method and application. The preparation method of the composite membrane of the present invention comprises: allowing the MXene dispersion to stand at room temperature to change from black to white, freeze-drying to obtain M-MXene powder; preparing the M-MXene powder into an M-MXene aqueous dispersion; adding hydrogen peroxide to the graphene oxide aqueous solution, stirring, freeze-drying to obtain PGO powder; preparing the PGO powder into a PGO aqueous dispersion; mixing the M-MXene aqueous dispersion and the PGO aqueous dispersion, and filtering on a cellulose membrane to obtain a MXene-graphene oxide composite membrane. The pure water flux of the composite membrane prepared by the present invention is 650Lm ‑2 h ‑ 1 bar ‑1 The above, and the removal rate of small molecule dyes in water is as high as more than 90%. The preparation method of the present invention is simple and easy to operate and easy to use on a large scale, which is conducive to promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of MXene materials, and in particular to a MXene-graphene oxide composite film and a preparation method and application thereof. Background Art

[0002] With the growth of population and the development of industry, more and more people are paying attention to how to treat water resources with affected water quality, such as industrial wastewater and domestic sewage. Membrane separation technology has been widely used in various wastewater treatment fields due to its high separation efficiency and environmental friendliness. The core of membrane separation technology lies in the membrane. Existing water treatment membranes include microfiltration, nanofiltration, ultrafiltration, forward and reverse osmosis, etc. However, most of the membranes are made of polymer materials and still face some problems, such as poor stability, acid and alkali resistance, and low pollutant retention rate. Moreover, there is a large restrictive relationship between its water flux and pollutant retention rate, making it difficult to achieve a two-way balance. Therefore, the development of new membrane materials with high water flux and high retention rate is still a major challenge.

[0003] As a popular two-dimensional material, MXene has become a star material for membrane separation technology due to its large specific surface area, abundant surface active sites, and high mechanical strength. However, the water flux of pure MXene film is small, and the retention rate of small molecules is low, which cannot meet the actual use needs. Based on this, compounding it with other materials has become a mainstream strategy. For example, the prior art discloses a method for preparing a graphene oxide / MXene composite membrane, and a GO / MXene composite membrane with a removal rate of small molecule dyes in water of 99.5% is obtained; the prior art discloses a new type of RGO / MXene composite membrane and its preparation method, and a MXene / RGO composite membrane with a Congo red dye retention rate of 98% is obtained; the prior art discloses a method for preparing a MXene / reduced porous graphene oxide (r-HGO) composite membrane with high flux and high removal rate, and the obtained MXene / r-HGO composite membrane has a dye retention rate of about 99%.

[0004] Although the above method improves the rejection rate of the composite membrane, the cost is a significant reduction in its water flux. Therefore, it is necessary to find a MXene-based composite membrane that can maintain a high rejection rate while having a high water flux. Summary of the invention

[0005] In view of this, the present invention proposes a MXene-graphene oxide composite film and a preparation method and application thereof, so as to solve or at least partially solve the defects existing in the prior art.

[0006] In a first aspect, the present invention provides a method for preparing a MXene-graphene oxide composite film, comprising the following steps:

[0007] The MXene dispersion was allowed to stand at room temperature to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0008] The M-MXene powder is formulated into an M-MXene aqueous dispersion;

[0009] Adding hydrogen peroxide to the graphene oxide aqueous solution, heating and stirring, and then freeze-drying to obtain PGO powder;

[0010] preparing PGO powder into a PGO aqueous dispersion;

[0011] The M-MXene aqueous dispersion and the PGO aqueous dispersion are mixed and filtered onto a cellulose membrane to obtain a MXene-graphene oxide composite membrane.

[0012] Preferably, the method for preparing the MXene dispersion comprises the following steps:

[0013] The MXene material is added to a mixed acid containing hydrofluoric acid, hydrochloric acid and water for etching, washed to neutrality, and the product is dispersed in an aqueous solution containing lithium chloride for intercalation, followed by centrifugation to obtain a MXene dispersion.

[0014] Preferably, the MXene dispersion is allowed to stand at room temperature for 20 to 40 days to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0015] The concentration of the M-MXene aqueous dispersion is 0.5 to 2 g / mL.

[0016] Preferably, the MXene material includes at least one of Ti3AlC2, Ti2AlC, Ti2AlN, Ti3AlN2, Ti4AlN3, Ti3AlCN, V2AlC, V3AlC2, V4AlC3, Nb2AlC, Nb3AlC2, Nb4AlC3, Mo2AlC, Mo3AlC2, Ta2AlC, Ta3AlC2, Ta4AlC3, Cr2AlC, TiNbAlC, TiVAlC, Ti2VAlC2, Ti2NbAlC2, Ti2TaAlC2, and Ti2Ta2AlC3.

[0017] Preferably, the mass volume ratio of the MXene material to the mixed acid is (2-4) g: (30-90) mL;

[0018] The volume ratio of hydrochloric acid, hydrofluoric acid and water in the mixed acid is (1-2):(1-2):(1-2);

[0019] The mass concentration of hydrochloric acid is 37-38%;

[0020] The mass concentration of hydrofluoric acid is 49-50%.

[0021] Preferably, the MXene material is added to a mixed acid containing hydrofluoric acid, hydrochloric acid and water, and etched at 30 to 50° C. for 8 to 12 hours.

[0022] Preferably, the product is dispersed in an aqueous solution containing 2 to 4 g of lithium chloride, stirred for 4 to 12 hours for intercalation, and then centrifuged at 3000 to 5000 rpm for 5 to 10 minutes, and the supernatant is taken to obtain a MXene dispersion.

[0023] Preferably, the concentration of the graphene oxide aqueous solution is 0.5 to 5 mg / mL;

[0024] The volume ratio of the graphene oxide aqueous solution to hydrogen peroxide is 1:(8-12);

[0025] Add hydrogen peroxide to the graphene oxide aqueous solution, heat and stir at 80-120° C. for 1-5 hours, and freeze-dry to obtain PGO powder; the mass concentration of hydrogen peroxide is 30-31%;

[0026] The concentration of the PGO aqueous dispersion is 0.5 to 5 mg / mL;

[0027] The mass ratio of the M-MXene aqueous dispersion to the PGO aqueous dispersion is 1:(1-3).

[0028] In a second aspect, the present invention also provides a MXene-graphene oxide composite film prepared by the preparation method.

[0029] In a third aspect, the present invention also provides an application of the MXene-graphene oxide composite membrane in removing dyes from wastewater.

[0030] The preparation method of the MXene-graphene oxide composite film of the present invention has the following advantages compared with the prior art:

[0031] Beneficial effects:

[0032] 1. The preparation method of the MXene-graphene oxide composite film of the present invention is to allow the MXene dispersion to stand at room temperature so that it changes from black to white, at which time the MXene dispersion deteriorates; specifically, the MXene dispersion is easily deteriorated into TiO2 after contacting dissolved oxygen, which greatly affects its electrical conductivity and mechanical properties; however, the oxidative deterioration of the MXene dispersion is similar to the process of in-situ growth of zero-dimensional TiO2 on a two-dimensional sheet material; this 0D / 2D structure helps its film formation and increases nano-water channels, thereby significantly improving its water flux; at the same time, this 0D / 2D deteriorated TiO2 is negatively charged and can effectively remove positively charged dyes by electrostatic adsorption. The present invention uses deteriorated M-MXene dispersion and PGO dispersion to prepare a deteriorated MXene-graphene oxide composite membrane with excellent comprehensive properties such as stable structure, high water flux, and high interception rate, so as to achieve the recycling and reuse of deteriorated MXene and apply it to the treatment of industrial wastewater;

[0033] 2. The pure water flux of the MXene-graphene oxide composite membrane prepared by the present invention is 650Lm -2 h -1 bar -1 The above, and the removal rate of small molecule dyes in water is as high as more than 90%. The preparation method of the present invention is simple and easy to operate and easy to use on a large scale, which is conducive to promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 is a SEM image of the MXene dispersion in step S1 of Example 1;

[0036] Figure 2 TEM image of TiO2 obtained in step S2 of Example 1;

[0037] Figure 3 is a SEM image of PGO obtained in step S4 of Example 1;

[0038] Figure 4 SEM images of the M-MXene / PGO composite films prepared in Examples 1 to 3, the MXene film prepared in Comparative Example 1, the M-MXene film prepared in Comparative Example 2, and the MXene / PGO composite films prepared in Comparative Examples 3 to 5;

[0039] Figure 5 XRD patterns of the M-MXene / PGO composite films prepared in Examples 1 to 3, the MXene film prepared in Comparative Example 1, the M-MXene film prepared in Comparative Example 2, and the MXene / PGO composite films prepared in Comparative Examples 3 to 5;

[0040] Figure 6 The pure water flux of the M-MXene / PGO composite membranes prepared in Examples 1 to 3, the MXene membrane prepared in Comparative Example 1, the M-MXene membrane prepared in Comparative Example 2, and the MXene / PGO composite membranes prepared in Comparative Examples 3 to 5;

[0041] Figure 7 It is the retention rate of small molecule dyes of the M-MXene / PGO composite membrane prepared in Examples 1 to 3, the MXene membrane prepared in Comparative Example 1, the M-MXene membrane prepared in Comparative Example 2, and the MXene / PGO composite membrane prepared in Comparative Examples 3 to 5. DETAILED DESCRIPTION

[0042] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0045] The present invention provides a method for preparing a MXene-graphene oxide composite film, comprising the following steps:

[0046] S1. The MXene dispersion is allowed to stand at room temperature to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0047] S2, preparing M-MXene powder into M-MXene aqueous dispersion;

[0048] S3, adding hydrogen peroxide to the graphene oxide aqueous solution, heating and stirring, and freeze-drying to obtain PGO powder;

[0049] S4, preparing PGO powder into PGO aqueous dispersion;

[0050] S5. After mixing the M-MXene aqueous dispersion and the PGO aqueous dispersion, the mixture is filtered on a cellulose membrane to obtain a MXene-graphene oxide composite membrane.

[0051] The preparation method of the MXene-graphene oxide composite film of the present invention is to place the MXene dispersion at room temperature so that it changes from black to white, and the MXene dispersion is deteriorated; specifically, the MXene dispersion is easy to deteriorate into TiO2 after contacting dissolved oxygen, which greatly affects its conductivity and mechanical properties; however, the oxidation deterioration of the MXene dispersion is similar to the process of in-situ growth of zero-dimensional TiO2 on a two-dimensional sheet material; this 0-dimensional / 2-dimensional structure helps its film formation and increases nano-water channels, thereby significantly improving its water flux; at the same time, this 0-dimensional / 2-dimensional deteriorated TiO2 is negatively charged and can effectively remove positively charged dyes by electrostatic adsorption. The present invention uses deteriorated M-MXene aqueous dispersion and PGO aqueous dispersion to prepare a deteriorated MXene-graphene oxide composite membrane with excellent comprehensive properties such as stable structure, high water flux, and high interception rate, so as to realize the recycling and reuse of deteriorated MXene and apply it to the treatment of industrial wastewater.

[0052] In some embodiments, a method for preparing a MXene dispersion comprises the following steps:

[0053] The MXene material is added to a mixed acid containing hydrofluoric acid, hydrochloric acid and water for etching, washed to neutrality, and the product is dispersed in an aqueous solution containing lithium chloride for intercalation, followed by centrifugation to obtain a MXene dispersion.

[0054] In some embodiments, the MXene dispersion is allowed to stand at room temperature (20-25° C.) for 20-40 days to change from black to white, and then freeze-dried to obtain M-MXene powder.

[0055] In some embodiments, the concentration of the M-MXene aqueous dispersion is 0.5 to 2 g / mL; specifically, the M-MXene powder is added to water to obtain the M-MXene aqueous dispersion.

[0056] In some embodiments, the MXene material includes at least one of Ti3AlC2, Ti2AlC, Ti2AlN, Ti3AlN2, Ti4AlN3, Ti3AlCN, V2AlC, V3AlC2, V4AlC3, Nb2AlC, Nb3AlC2, Nb4AlC3, Mo2AlC, Mo3AlC2, Ta2AlC, Ta3AlC2, Ta4AlC3, Cr2AlC, TiNbAlC, TiVAlC, Ti2VAlC2, Ti2NbAlC2, Ti2TaAlC2, and Ti2Ta2AlC3.

[0057] In some embodiments, the mass volume ratio of MXene material to mixed acid is (2-4) g: (30-90) mL;

[0058] In some embodiments, the volume ratio of hydrochloric acid, hydrofluoric acid and water in the mixed acid is (1-2):(1-2):(1-2); the mass concentration of hydrochloric acid is 37-38%, and the mass concentration of hydrofluoric acid is 49-50%.

[0059] In some embodiments, the MXene material is added to a mixed acid containing hydrofluoric acid, hydrochloric acid and water, and etched at 30 to 50° C. for 8 to 12 hours.

[0060] In some embodiments, the product is dispersed in an aqueous solution containing 2 to 4 g of lithium chloride, stirred for 4 to 12 hours for intercalation, and then centrifuged at 3000 to 5000 rpm for 5 to 10 minutes, and the supernatant is taken to obtain a MXene dispersion.

[0061] In some embodiments, the concentration of the graphene oxide aqueous solution is 0.5-5 mg / mL; specifically, the graphene oxide aqueous solution is obtained by adding graphene oxide to water.

[0062] In some embodiments, the volume ratio of graphene oxide aqueous solution to hydrogen peroxide is 1:(8-12);

[0063] In some embodiments, hydrogen peroxide is added to a graphene oxide aqueous solution, heated and stirred at 80-120° C. for 1-5 hours, and freeze-dried to obtain PGO powder; the mass concentration of hydrogen peroxide is 30-31%.

[0064] In some embodiments, the concentration of the PGO aqueous dispersion is 0.5-5 mg / mL. Specifically, PGO powder is added to water to obtain the PGO aqueous dispersion.

[0065] In some embodiments, the mass ratio of the M-MXene aqueous dispersion to the PGO aqueous dispersion is 1:(1-3).

[0066] The pure water flux of the MXene-graphene oxide composite membrane prepared by the present invention is 650Lm -2 h -1 bar -1 The above, and the removal rate of small molecule dyes in water is as high as more than 90%. The preparation method of the invention is simple and easy to operate and easy to use on a large scale, which is conducive to promotion.

[0067] Based on the same inventive concept, the present invention also provides a MXene-graphene oxide composite film, which is prepared by the above-mentioned preparation method.

[0068] Based on the same inventive concept, the present invention also provides an application of the above-mentioned MXene-graphene oxide composite membrane in removing dyes from wastewater.

[0069] Specifically, the MXene-graphene oxide composite membrane prepared by the present invention can remove dyes in wastewater, including but not limited to positively charged dyes such as rhodamine B (RhB) and methylene blue (MB), and negatively charged dyes such as methyl orange (MO).

[0070] The following further illustrates the MXene-graphene oxide composite film of the present application and its preparation method and application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0071] In the following examples, titanium aluminum carbide (Ti3AlC2) is a commercially available product.

[0072] Example 1

[0073] The present invention provides a method for preparing a MXene-graphene oxide composite film, comprising the following steps:

[0074] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0075] S2, the MXene dispersion in S1 was allowed to stand at room temperature for 30 days to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0076] S3, preparing the M-MXene powder in S2 into a 1 mg / mL M-MXene aqueous dispersion;

[0077] S4, transferring 200 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 20 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 4 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0078] S5, preparing the PGO powder in S4 into a 1 mg / mL PGO aqueous dispersion;

[0079] S6. Mix the M-MXene aqueous dispersion in S3 and the PGO aqueous dispersion in S5 in a mass ratio of 1:1 (5 mg in total), add 15 mL of ultrapure water and mix ultrasonically for 0.5 h, and use a vacuum filtration device to filter on a cellulose membrane to obtain an M-MXene / PGO composite membrane, which is a MXene-graphene oxide composite membrane.

[0080] Example 2

[0081] The present invention provides a method for preparing a MXene-graphene oxide composite film, comprising the following steps:

[0082] S1. Add 3 g of Ti3AlC2 to a mixed acid of 30 mL of hydrofluoric acid (mass concentration 49%), 30 mL of hydrochloric acid (mass concentration 37%) and 30 mL of water, etch at 35 ° C for 12 h, wash to neutrality, disperse the product in an aqueous solution (50 mL of water) containing 3 g of lithium chloride, stir for 12 h for intercalation, and then centrifuge at 3500 rpm for 5 min, take the supernatant, and obtain a MXene dispersion;

[0083] S2, the MXene dispersion in S1 was allowed to stand at room temperature for 30 days to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0084] S3, preparing the M-MXene powder in S2 into a 1 mg / mL M-MXene aqueous dispersion;

[0085] S4, transferring 100 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 10 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 5 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0086] S5, preparing the PGO powder in S4 into a 1 mg / mL PGO aqueous dispersion;

[0087] S6. Mix the M-MXene aqueous dispersion in S3 and the PGO aqueous dispersion in S5 in a mass ratio of 1:2 (5 mg in total), add 15 mL of ultrapure water and perform ultrasonic mixing for 0.5 h, and use a vacuum filtration device to filter on a cellulose membrane to obtain an M-MXene / PGO composite membrane, which is a MXene-graphene oxide composite membrane.

[0088] Example 3

[0089] The present invention provides a method for preparing a MXene-graphene oxide composite film, comprising the following steps:

[0090] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0091] S2, the MXene dispersion in S1 was allowed to stand at room temperature for 30 days to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0092] S3, preparing the M-MXene powder in S2 into a 1 mg / mL M-MXene aqueous dispersion;

[0093] S4, transferring 200 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 20 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 4 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0094] S5, preparing the PGO powder in S4 into a 1 mg / mL PGO aqueous dispersion;

[0095] S6. Mix the M-MXene aqueous dispersion in S3 and the PGO aqueous dispersion in S5 in a mass ratio of 1:3 (5 mg in total), add 15 mL of ultrapure water and mix ultrasonically for 0.5 h, and use a vacuum filtration device to filter on a cellulose membrane to obtain an M-MXene / PGO composite membrane, which is a MXene-graphene oxide composite membrane.

[0096] Comparative Example 1

[0097] This comparative example provides a method for preparing a MXene film, comprising the following steps:

[0098] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0099] S2, preparing the MXene dispersion in S1 into a 1 mg / mL MXene aqueous dispersion;

[0100] S3. Add 15 mL of ultrapure water to 5 mL of MXene aqueous dispersion in S2 and mix ultrasonically for 0.5 h. Use a vacuum filtration device to filter on the cellulose membrane to obtain a MXene membrane.

[0101] Comparative Example 2

[0102] This comparative example provides a method for preparing an M-MXene film, comprising the following steps:

[0103] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0104] S2, the MXene dispersion in S1 was allowed to stand at room temperature for 30 days to change from black to white, and then freeze-dried to obtain M-MXene powder;

[0105] S3, preparing the M-MXene powder in S2 into a 1 mg / mL M-MXene aqueous dispersion;

[0106] S4. Add 15 mL of ultrapure water to 5 mL of the M-MXene aqueous dispersion in S3 and mix ultrasonically for 0.5 h. Use a vacuum filtration device to filter on the cellulose membrane to obtain the M-MXene membrane.

[0107] Comparative Example 3

[0108] This comparative example provides a method for preparing a MXene / PGO composite film, comprising the following steps:

[0109] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0110] S2, preparing the MXene dispersion in S1 into a 1 mg / mL MXene aqueous dispersion;

[0111] S3, transferring 200 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 20 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 4 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0112] S4, preparing the PGO powder in S3 into a 1 mg / mL PGO aqueous dispersion;

[0113] S5. Mix the MXene aqueous dispersion in S2 and the PGO aqueous dispersion in S4 in a mass ratio of 1:1 (5 mg in total), add 15 mL of ultrapure water and mix ultrasonically for 0.5 h, and use a vacuum filtration device to filter on the cellulose membrane to obtain a MXene / PGO composite membrane.

[0114] Comparative Example 4

[0115] This comparative example provides a method for preparing a MXene / PGO composite film, comprising the following steps:

[0116] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0117] S2, preparing the MXene dispersion in S1 into a 1 mg / mL MXene aqueous dispersion;

[0118] S3, transferring 200 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 20 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 4 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0119] S4, preparing the PGO powder in S3 into a 1 mg / mL PGO aqueous dispersion;

[0120] S5. Mix the MXene aqueous dispersion in S2 and the PGO aqueous dispersion in S4 in a mass ratio of 1:2 (5 mg in total), add 15 mL of ultrapure water and mix ultrasonically for 0.5 h, and use a vacuum filtration device to filter on the cellulose membrane to obtain a MXene / PGO composite membrane.

[0121] Comparative Example 5

[0122] This comparative example provides a method for preparing a MXene / PGO composite film, comprising the following steps:

[0123] S1. Add 3g Ti3AlC2 to a mixed acid of 30mL hydrofluoric acid (mass concentration 49%), 30mL hydrochloric acid (mass concentration 37%) and 30mL water, etch at 35°C for 12h, wash to neutrality, disperse the product in an aqueous solution of 3g lithium chloride (50mL water), stir for 12h for intercalation, then centrifuge at 3500rpm for 5min, take the supernatant, and obtain a MXene dispersion;

[0124] S2, preparing the MXene dispersion in S1 into a 1 mg / mL MXene aqueous dispersion;

[0125] S3, transferring 200 mL of 1 mg / mL graphene oxide aqueous solution into a beaker, adding 20 mL of hydrogen peroxide (mass concentration of 30%) and stirring, then sealing and placing in an oil bath and heating and stirring at 100° C. for 4 h to obtain a PGO solution, which was freeze-dried to obtain a PGO powder;

[0126] S4, preparing the PGO powder in S3 into a 1 mg / mL PGO aqueous dispersion;

[0127] S5. Mix the MXene aqueous dispersion in S2 and the PGO aqueous dispersion in S4 in a mass ratio of 1:3 (5 mg in total), add 15 mL of ultrapure water and mix ultrasonically for 0.5 h, and use a vacuum filtration device to filter on the cellulose membrane to obtain a MXene / PGO composite membrane.

[0128] Performance Testing

[0129] Figure 1 This is the SEM image of the MXene dispersion in step S1 of Example 1. It can be seen that the obtained MXene is a complete two-dimensional sheet material with no oxidized TiO2 generated on the surface.

[0130] Figure 2 This is a TEM image of TiO2 obtained in step S2 of Example 1. It can be seen that the structure of the obtained TiO2 is an obvious 0-dimensional / 2-dimensional porous structure, which is helpful to construct water channels in the composite membrane.

[0131] Figure 3 This is a SEM image of the PGO obtained in step S4 of Example 1. The obtained PGO still retains a complete two-dimensional lamellar structure.

[0132] Figure 4 SEM images of the M-MXene / PGO composite films prepared in Examples 1 to 3, the MXene film prepared in Comparative Example 1, the M-MXene film prepared in Comparative Example 2, and the MXene / PGO composite films prepared in Comparative Examples 3 to 5.

[0133] Figure 4 Wherein a is the MXene film prepared in Comparative Example 1, b is the MXene / PGO composite film prepared in Comparative Example 3, c is the MXene / PGO composite film prepared in Comparative Example 4, d is the MXene / PGO composite film prepared in Comparative Example 5, e is the M-MXene film prepared in Comparative Example 2, f is the M-MXene / PGO composite film prepared in Example 1, g is the M-MXene / PGO composite film prepared in Example 2, and h is the M-MXene / PGO composite film prepared in Example 3.

[0134] from Figure 4 It can be seen that the pure MXene film in Comparative Example 1 ( Figure 4 The surface of a) does not show obvious water channels, which also makes its water flux small, and the change is still weak even after adding PGO ( Figure 4 b, c, d); while the surface of the pure M-MXene membrane in Comparative Example 2 shows an obvious pore structure, which is beneficial to the increase of its water flux, but will lead to a lower dye retention rate; the addition of PGO significantly improves the film-forming properties of the composite membrane ( Figure 4In f, g, and h), although the water flux is reduced, the dye retention rate is greatly improved.

[0135] Figure 5 XRD patterns of the M-MXene / PGO composite films prepared in Examples 1 to 3, the MXene film prepared in Comparative Example 1, the M-MXene film prepared in Comparative Example 2, and the MXene / PGO composite films prepared in Comparative Examples 3 to 5.

[0136] Figure 5 In the figure a, MXene represents the MXene film prepared in Comparative Example 1, 1:1 represents the MXene / PGO composite film prepared in Comparative Example 3, 1:2 represents the MXene / PGO composite film prepared in Comparative Example 4, and 1:3 represents the MXene / PGO composite film prepared in Comparative Example 5; Figure 5 In Figure b, M-MXene represents the M-MXene film prepared in Comparative Example 2, PGO represents the PGO powder prepared in Example 1, 1:1 represents the M-MXene / PGO composite film prepared in Example 1, 1:2 represents the M-MXene / PGO composite film prepared in Example 2, and 1:3 represents the M-MXene / PGO composite film prepared in Example 3.

[0137] from Figure 5 It can be seen that the (002) peak of the MXene / PGO composite membranes prepared in Comparative Examples 3 to 5 gradually shifts to the right, that is, the interlayer spacing of the composite membranes decreases, resulting in a lower water flux. The (002) peak of the M-MXene / PGO composite membranes prepared in Examples 1 to 3 is located between PGO and M-MXene, indicating that the two are evenly mixed.

[0138] Figure 6 It is the pure water flux of the M-MXene / PGO composite membrane prepared in Examples 1 to 3, the MXene membrane prepared in Comparative Example 1, the M-MXene membrane prepared in Comparative Example 2, and the MXene / PGO composite membrane prepared in Comparative Examples 3 to 5.

[0139] Figure 6 MXene:PGO, in which the abscissa MXene represents the MXene film prepared in Comparative Example 1, 1:1 represents the MXene / PGO composite film prepared in Comparative Example 3, 1:2 represents the MXene / PGO composite film prepared in Comparative Example 4, and 1:3 represents the MXene / PGO composite film prepared in Comparative Example 5; Figure 6In the M-MXene:PGO, the horizontal axis M-MXene represents the M-MXene film prepared in Comparative Example 2, PGO represents the PGO powder prepared in Example 1, 1:1 represents the M-MXene / PGO composite film prepared in Example 1, 1:2 represents the M-MXene / PGO composite film prepared in Example 2, and 1:3 represents the M-MXene / PGO composite film prepared in Example 3.

[0140] The water flux calculation formula is:

[0141] J = v / (A×t×P)

[0142] Where, v is the filtrate volume (L), A is the effective membrane area (m 2 ), t represents the filtration time (h), P represents the filtration pressure (bar), and in the embodiment, the effective membrane area is 12.56 cm 2 , the filtration pressure is 0.1 bar.

[0143] from Figure 6 It can be seen that the water flux of the MXene membrane prepared in Comparative Example 1 is 84.62Lm -2 h -1 bar -1 The water flux of the MXene / PGO composite membrane prepared in Comparative Example 3 is 142.45 Lm -2 h -1 bar -1 The water flux of the MXene / PGO composite membrane prepared in Comparative Example 4 is 92.18 Lm -2 h -1 bar -1 The water flux of the MXene / PGO composite membrane prepared in Comparative Example 5 is 79.86 Lm -2 h -1 bar -1 The water flux of the M-MXene membrane prepared in Comparative Example 2 is 5193.42 Lm -2 h -1 bar -1 The water flux of the M-MXene / PGO composite membrane prepared in Example 1 was 807.31 Lm -2 h -1 bar -1 The water flux of the M-MXene / PGO composite membrane prepared in Example 2 was 725.51 Lm -2 h -1 bar -1 The water flux of the M-MXene / PGO composite membrane prepared in Example 3 was 687.59 Lm -2 h -1 bar -1.

[0144] Figure 7 The retention rates of small molecule dyes by the M-MXene / PGO composite membranes prepared in Examples 1 to 3, the MXene membranes prepared in Comparative Example 1, the M-MXene membranes prepared in Comparative Example 2, and the MXene / PGO composite membranes prepared in Comparative Examples 3 to 5 are all 0.1 mg / mL in concentration of the small molecule dyes, wherein rhodamine B (RhB) and methylene blue (MB) are positively charged dyes, and methyl orange (MO) is a negatively charged dye.

[0145] Figure 7 In the figure a, the horizontal axis MXene represents the MXene film prepared in Comparative Example 1, 1:1 represents the MXene / PGO composite film prepared in Comparative Example 3, 1:2 represents the MXene / PGO composite film prepared in Comparative Example 4, and 1:3 represents the MXene / PGO composite film prepared in Comparative Example 5; Figure 7 In Figure b, the horizontal axis M-MXene represents the M-MXene film prepared in Comparative Example 2, PGO represents the PGO powder prepared in Example 1, 1:1 represents the M-MXene / PGO composite film prepared in Example 1, 1:2 represents the M-MXene / PGO composite film prepared in Example 2, and 1:3 represents the M-MXene / PGO composite film prepared in Example 3.

[0146] The dye retention rate formula is:

[0147] R=(1-C p / C f )×100%.

[0148] C p and C f Represent the concentration of the membrane solution and the original solution (mg / L), respectively.

[0149] from Figure 7It can be seen that the MXene film prepared in Comparative Example 1, the MXene / PGO composite film prepared in Comparative Examples 3 to 5, the M-MXene film prepared in Comparative Example 2, and the M-MXene / PGO composite film prepared in Examples 1 to 3 have a rejection rate of 50.49%, 81.64%, 86.19%, 91.94%, 78.21%, 93.26%, 93.66%, and 93.46% for rhodamine B, respectively; the MXene film prepared in Comparative Example 1, the MXene / PGO composite film prepared in Comparative Examples 3 to 5, the M-MXene film prepared in Comparative Example 2, and the M-MXene / PGO composite film prepared in Examples 1 to 3 have a rejection rate of 50.49%, 81.64%, 86.19%, 91.94%, 78.21%, 93.26%, 93.66%, and 93.46% for methylene blue, respectively. The retention rates of methyl orange were 33.96%, 87.65%, 97.98%, 98.73%, 90.29%, 99.33%, 99.77% and 99.74%, respectively; the MXene film prepared in Comparative Example 1, the MXene / PGO composite film prepared in Comparative Examples 3 to 5, the M-MXene film prepared in Comparative Example 2, and the M-MXene / PGO composite film prepared in Examples 1 to 3 were 5.19%, 7.63%, 10.94%, 13.83%, 7.92%, 8.62%, 12.58% and 11.37%, respectively; it can be seen that the MXene / PGO composite film prepared by the present invention exhibits efficient retention of positively charged small molecule dyes.

[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MXene-graphene oxide composite film, characterized in that: The following steps are involved: The MXene dispersion was allowed to stand at room temperature for 20 to 40 days to change from black to white, and then freeze-dried to obtain M-MXene powder. The M-MXene powder is formulated into an M-MXene aqueous dispersion; Adding hydrogen peroxide to the graphene oxide aqueous solution, heating and stirring, and then freeze-drying to obtain PGO powder; preparing PGO powder into a PGO aqueous dispersion; After mixing the M-MXene aqueous dispersion and the PGO aqueous dispersion, the mixture was filtered on a cellulose membrane to obtain a MXene-graphene oxide composite membrane; The method for preparing the MXene dispersion comprises the following steps: The MXene material is added to a mixed acid containing hydrofluoric acid, hydrochloric acid and water for etching, washed to neutrality, and the product is dispersed in an aqueous solution containing lithium chloride for intercalation, and then centrifuged to obtain a MXene dispersion; The concentration of the M-MXene aqueous dispersion is 0.5-2 g / mL; The concentration of the PGO aqueous dispersion is 0.5-5 mg / mL; The mass ratio of the M-MXene aqueous dispersion to the PGO aqueous dispersion is 1:(1-3).

2. The method for preparing a MXene-graphene oxide composite film according to claim 1, wherein: The MXene material includes at least one of Ti3AlC2, Ti2AlC, Ti2AlN, Ti3AlN2, Ti4AlN3, Ti3AlCN, V2AlC, V3AlC2, V4AlC3, Nb2AlC, Nb3AlC2, Nb4AlC3, Mo2AlC, Mo3AlC2, Ta2AlC, Ta3AlC2, Ta4AlC3, Cr2AlC, TiNbAlC, TiVAlC, Ti2VAlC2, Ti2NbAlC2, Ti2TaAlC2, and Ti2Ta2AlC3.

3. The method for preparing a MXene-graphene oxide composite film according to claim 1, wherein: The mass volume ratio of the MXene material to the mixed acid is (2-4) g: (30-90) mL; The volume ratio of hydrochloric acid, hydrofluoric acid and water in the mixed acid is (1-2):(1-2):(1-2); The mass concentration of hydrochloric acid is 37~38%; The mass concentration of hydrofluoric acid is 49~50%.

4. The method for preparing a MXene-graphene oxide composite film according to claim 1, wherein: Add the MXene material to a mixed acid containing hydrofluoric acid, hydrochloric acid and water, and etch it at 30~50℃ for 8~12h.

5. The method for preparing a MXene-graphene oxide composite film according to claim 1, wherein: The product was dispersed in an aqueous solution containing 2-4 g of lithium chloride, stirred for 4-12 h for intercalation, and then centrifuged at 3000-5000 rpm for 5-10 min. The supernatant was taken to obtain a MXene dispersion.

6. The method for preparing a MXene-graphene oxide composite film according to claim 1, wherein: The concentration of the graphene oxide aqueous solution is 0.5-5 mg / mL; The volume ratio of the graphene oxide aqueous solution to hydrogen peroxide is 1:(8-12); Hydrogen peroxide is added to the graphene oxide aqueous solution, heated and stirred at 80-120° C. for 1-5 hours, and freeze-dried to obtain PGO powder; the mass concentration of hydrogen peroxide is 30-31%.

7. A MXene-graphene oxide composite film, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the MXene-graphene oxide composite membrane as claimed in claim 7 in removing dyes from wastewater.

Citation Information

Patent Citations

  • Preparation method and application of graphene oxide / MXene composite film

    CN110124529A

  • MXene-GO composite membrane with humidity response as well as preparation method and application thereof

    CN112999885A